Combinatorial Stochastic Processes Ecole d'Eté de Probabilités de Saint-Flour XXXII - 2002 - Pitman, Jim (École d'Été de Probabilités de Saint-Flour ;, 2006)
Three series of lectures were given at the 32nd Probability Summer School in Saint-Flour (July 7-24, 2002), by the Professors Pitman, Tsirelson and Werner. ThecoursesofProfessorsTsirelson("Scalinglimit,noise,stability")andWerner ("Random planar curves and Schramm-Loewner evolutions") have been p- lished in a previous issue ofLectures Notes in Mathematics (volume 1840). This volume contains the course "Combinatorial stochastic processes" of Professor Pitman. We cordially thank the author for his performance in Saint-Flour and for these notes. 76 participants have attended this school. 33 of them have given a short lecture. The lists of participants and of short lectures are enclosed at the end of the volume. The Saint-Flour Probability Summer School was founded in 1971. Here are the references of Springer volumes which have been published prior to this one. All numbers refer to theLecture Notes in Mathematics series,except S-50 which refers to volume 50 of the Lecture Notes in Statistics series. 1971: vol 307 1980: vol 929 1990: vol 1527 1998: vol 1738 1973: vol 390 1981: vol 976 1991: vol 1541 1999: vol 1781 1974: vol 480 1982: vol 1097 1992: vol 1581 2000: vol 1816 1975: vol 539 1983: vol 1117 1993: vol 1608 2001: vol 1837 & 1851 1976: vol 598 1984: vol 1180 1994: vol 1648 2002: vol 1840 1977: vol 678 1985/86/87: vol 1362 & S-50 1995: vol 1690 2003: vol 1869 1978: vol 774 1988: vol 1427 1996: vol 1665 1979: vol 876 1989: vol 1464 1997: vol 1717.